(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the efficacy of auricular acupuncture in treating insomnia in the late recovery or chronic phase following a stroke. Subject and method: This is a randomized, double-blind, controlled clinical trial conducted on 60 post-stroke patients with insomnia at the Ho Chi Minh City Traditional Medicine Hospital from December 2023 to June 2024. Patients were randomly assigned to two groups: the study group (auricular acupuncture + standard treatment) and the control group (sham auricular acupuncture + standard treatment). Sleep indices were monitored and assessed using the PSQI score at 0, 5, 10, 15, and 30 days. Results: After 30 days, the study group showed significant improvements in sleep onset latency (1.27 ± 0.45 and 1.60 ± 0.62 in the control group, p<0.05 from day 10), total sleep time, and sleep efficiency (p<0.05 from day 15). They also reduced sleep medication use and improved sleep quality compared to the control group (p<0.05). The PSQI score in the study group dropped significantly over time: Day 5 (15.03 ± 2.52), Day 10 (11.40 ± 2.06), Day 15 (7.73 ± 2.21), and Day 30 (6.87 ± 1.85) (p<0.05 from day 10). No adverse effects were observed. Conclusion: Auricular acupuncture combined with standard treatment significantly improves sleep quality in post-stroke insomnia patients and is safe to use. Auricular acupuncture may serve as an effective adjunct therapy during the late recovery or chronic phase after stroke.